Parental kidnapping as a form of abuse of parental rights - O. G. Yushkevych; M. Yu. Burdin (Bulletin of Kharkiv National University of Internal Affairs)
The article explores the legal phenomenon of “parental kidnapping”. It is noted that Ukrainian legislation lacks a definition of this legal phenomenon. The author suggests understanding parental kidnapping as the action of one of the parents regarding the unauthorized change of the child’s place of residence without the consent of the other parent with whom, according to the law or a court decision, the child resides. This includes abduction, leading to a violation of the child’s rights and causing material or non-material harm.